PENGARUH KUALITAS PRODUK, HARGA DAN KUALITAS PELAYANAN PADA KEPUTUSAN PEMBELIAN PROSHOP PERMATA SENTUL GOLF - Arnas Nasution, Nurayla; Nur Rahmadesianingrum, Ekanantri (Economicus, 2023)
This study aims to determine the effect of Product Quality (X1), Price (X2) and Service Quality (X3) on Purchasing Decisions (Y) at Proshop Permata Sentul Golf. This research method uses a causality method that aims to know deeply and thoroughly the cause and effect relationship as well as to find out how the relationship between variables and problems refers to the purpose of the study. The collection of research data was carried out using a closed questionnaire technique (questionnaire) distributed to 100 respondents. Based on the t test, it shows that the results of the variables Product Quality (X1), Price (X2) and Service Quality (X3) < 0.1, then H0 is rejected and Ha is accepted, meaning that variables X1, X2 and X3 have a significant partial influence on the Purchase Decision at Proshop Permata Sentul Golf. Based on the f test shows that the Sig value of 0.000 < 0.1 then H0 is rejected and Ha is accepted, using a significance level of 10% (0.1), Fcalculate 147.975 > Ftable 2.14 it can be concluded that there is a significant influence simultaneously or together between the variables Product Quality (X1), Price (X2) and Service Quality (X3) on the Purchase Decision variable (Y). The large value of the coefficient of determination shows that the variables Product Quality, Price and Service Quality are able to explain the Purchase Decision variable by 81.7%. While the remaining 18.3% was influenced by other factors that were not included in this research model.